1999
DOI: 10.1002/(sici)1521-3935(19990401)200:4<852::aid-macp852>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

FTIR spectroscopic studies of interfacial reactions between amino functionalized silicon surfaces and molten maleic anhydride copolymers

Abstract: SUMMARY: The interactions of two reactive maleic anhydride copolymers, a styrene maleic anhydride copolymer and an alternating copolymer of malic anhydride and a-olefin side chains, with amino-functionalized surfaces were studied by means of FTIR-ATR spectroscopy. The interfacial processes were detected at a planar surface of a thermally oxidized silicon as internal reflecting element. This ATR element can be understood as a model for a glass fiber which is used as reinforcing material in polymer matrices. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…The success of this thermal treatment was determined by FT-IR spectroscopy. [4] c-APS was obtained from Aldrich and used as received.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The success of this thermal treatment was determined by FT-IR spectroscopy. [4] c-APS was obtained from Aldrich and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…By FT-IR ATR spectroscopy it could be shown that this layer consists of a highly crosslinked aminosiloxane network containing NH 2 -and NH 3 + -functional groups. [4] The mean roughness of these surfaces determined from images of 10 lm 6 10 lm was in the order of several nanometers (S a L 5 nm) compared to the bare silicon wafers having a mean roughness of S a = 0.5 nm. Contact angle measurements yielded an advancing water contact angle of 61.5 l 1.6 8 and receding angles of about 30 8.…”
Section: Surface Properties and Chemical Composition Of The Solid Submentioning
confidence: 99%
See 1 more Smart Citation
“…2b), the absorbance bands at 2923 and 2852 cm -1 are assigned to asymmetric and symmetric stretching vibration of >CH 2 , the strong and broad peak at 1029 cm -1 is the typical stretching absorbance band of Si-O-Si. The absorbance bands between 1650~1130 cm -1 are attributed to the stretching vibration of carbonyl group and bicarbonate salts due to the interaction between the amino group of γ-APS based components and environmental CO 2 and water Page 8 of 22 [34,35]. From the similarity between Fig.…”
Section: Analyses On Extractionsmentioning
confidence: 99%
“…It is noted that θ a of APS fibre is about 83.5°. This value is higher than the expected one (40-68°) [40,41] but still reasonable basing on following two reasons. (i) It was proposed that the electron pair on the amine nitrogen could point toward the glass surface, sideways, or toward free air [3, 26-28, 34, 42-44].…”
Section: Surface Properties Of Sized Gfsmentioning
confidence: 99%